A new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from Yunnan, China and its phylogenetic relationship to other congeners - Agung, Ade Prasetyo; Grismer, L. Lee; Grismer, Jesse L.; Quah, Evan S. H.; Chornelia, Ada; Lu, Jianmei; Hughes, Alice C. (Zootaxa, 2021)
A new species of the gekkonid genus Hemiphyllodactylus is described from forested karst hills near Zhutangxiang town, Lancang Lahu Autonomous County, Yunnan, China. Hemiphyllodactylus zhutangxiangensis sp. nov. is distinguished from all other congeners in morphology and an uncorrected pairwise sequence divergence of greater than 14% based on 1039 base pairs of the mitochondrial NADH dehydrogenase subunit 2 gene (ND2). The new species is defined by the following characters: a maximum SVL of 44.42 mm; 7–9 chin scales; enlarged postmentals; five circumnasal scales; 2–4 internasal scales; 8–11 supralabial scales; 8–11 infralabial scales; subdigital lamellae on fingers II–V (3–5)-(4–6)-(4 or 5)-(4 or 5); subdigital lamellae on toes II–V (4 or 5)-(4 or 5)-(4–6)-(4 or 5); dorsal scales 11–15; ventral scales 5–7; 20–23 continuous femoroprecloacal pores; having pale-grey base color on the body with various darker transverse dorsal blotches; a dark postorbital stripe extending to at least to the base of the neck; no dark dorsolateral or ventrolateral stripe on trunk; and postsacral marking bearing a dark fork-like pattern with anteriorly projecting arms. The new species brings the species total of Hemiphyllodactylus in China to 11.